Determination Of Notary Service Fees For The Preparation Of Authentic Deeds In Payakumbuh City - Rani Permata Sari; Ali Arben (jurnal.unprimdn.ac.id, 2026)
The emergence of improper competition among notaries is partly due to the imposition of service charges or honorariums that are lower than the provisions outlined in the Law and the Ethical Guidelines. This is very contrary to what is regulated by the UUJN and the Notary Code of Ethics, because notaries are prohibited from making efforts to determine service rates below the standard to get as many clients as possible, but in practice there are notaries who do this. For this reason, in cases like this, there needs to be supervision by the Notary Supervisory Board regarding the implementation of Notary honorariums.